Simulation of PUE Attack Detection using Transmitter Locations and Modulation Techniques in CRNs - Mahesh Kumar N, Siddesh G.K. (International Journal of Advanced Science and Technology, 2020)
In this research article, we present the Matlab Simulation of PUE attack conceptual developmentusing mitigation techniques based transmitter locations with received signal strength (RSS),feature detection (FD) & power estimation method (PEM) using Power Spectral Density (PSD).We know that the growth in wireless communications has increased the demand for wirelessradio spectrum to utilize many social and individual benefits. Cognitive radio is a technologythat provides a possible solution for improving the spectrum efficiency by allowing opportunisticaccess to the spectrum for unlicensed users (CRs). In this work, we mainly focus on PrimaryUser Emulation attack (PUEA) is one such major threat posed on spectrum sensing, whichdecreases the spectrum access probability. In this work, we mainly focus on Primary UserEmulation attack (PUEA) & this is one such major threat posed on spectrum sensing, whichdecreases the spectrum access probability. We had proposed the mitigation techniques basedtransmitter location using received signal strength (RSS) and based on feature detection (FD),which employs a cyclostationary calculation (CC) to represent the modulation features of theuser signals using a mathematical model, which was the subject of another paper.Principle ofoperation of the detection of the primary signal & the malicious signal transmitter during thespectrum sensing period along with the data flow diagram used for the simulation purposes forthe observation of the results is presented in this context. The .m code is developed as per theproposed algorithms, the simulation is run for requisite amount of time and the simulationresults are observed such asthe graphs of SCF of AWGN noise signal ; SCF of the primary usersignal with FM modulation technique ; SCF of the primary user signal with FM modulationtechnique at SNR ∞, 3 dB and –3dB ; SCF of the Malicious user signal with QPSK modulationtechnique at SNR ∞, 3dB and –3 dB ; Probability of false alarm ; Probability of misdetection ;Power estimation for both proposed Localization and PSD at PUE mitigation ; Probability offalse alarm and misdetection of both proposed Localization and PSD ; The localization errorsand computation time of the localization system are observed. The simulation results show thatthe system performance of the power estimation method using PSD is better than the localizationdetection method using RSS in the presence of PUEA, in the other words, the results portray theeffectiveness of the methodology proposed in this research paper.